PENGARUH BEBAN KERJA DAN KOMPETENSI TERHADAP KEPUASAN KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) KABUPATEN BULELENG - Mahadi Karang, Gede Krisna; Yulianthini, Ni Nyoman (LPPM - STIE SAKTI ALAM KERINCI, 2026)
This study aims to determine the effect of workload and competence on employee job satisfaction at the Civil Service and Human Resources Development Agency of Buleleng Regency. The approach used is quantitative with a causal research type, through a survey method using a Likert scale questionnaire that has been tested for validity and reliability. The population in this study were all ASN employees at the BKPSDM of Buleleng Regency with a sampling technique using the saturated sample method, so that the entire population was used as research respondents, namely 48 employees. Data were analyzed using the classical assumption test and multiple linear regression. The results of the study indicate that: (1) workload has a negative and significant effect on job satisfaction, (2) competence has a positive and significant effect on job satisfaction, and (3) simultaneously, workload and competence have a significant effect on job satisfaction. The R Square value of 0.551 indicates that the workload and competence variables are able to explain 55.1% of the variation in job satisfaction, while the rest is influenced by other variables outside the study. This finding confirms that proportional workload management and continuous competency improvement are important factors in increasing job satisfaction in the BKPSDM of Buleleng Regency.